2015
DOI: 10.1186/s12879-015-1094-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum inorganic phosphorus levels predict 30-day mortality in patients with community acquired pneumonia

Abstract: BackgroundCommunity acquired pneumonia is a major cause of morbidity and mortality. The association between serum phosphorus levels on admission and the outcome of patients with community acquired pneumonia has not been widely examined. We aimed to investigate the prognostic value of serum phosphorus levels on admission on the 30- day mortality.MethodsThe cohort included patients of 18 years old or older who were diagnosed with community acquired pneumonia between 2006 and 2012. Patients were retrospectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Transient hypophosphatemia is also observed in both children and adults in the course of diagnosed infections; phosphorus concentration is inversely proportionate to C-reactive protein (CRP) level, so other anti-inflammatory factors are said to take part in the process (tumor necrosis factor alpha and interleukin 6). 22,23 When should phosphorus concentration be monitored, then? Unfortunately, there are no generally accepted protocols, but there is increasing evidence which indicates that it is important to measure phosphate concentration within the first days of life.…”
Section: Discussionmentioning
confidence: 99%
“…Transient hypophosphatemia is also observed in both children and adults in the course of diagnosed infections; phosphorus concentration is inversely proportionate to C-reactive protein (CRP) level, so other anti-inflammatory factors are said to take part in the process (tumor necrosis factor alpha and interleukin 6). 22,23 When should phosphorus concentration be monitored, then? Unfortunately, there are no generally accepted protocols, but there is increasing evidence which indicates that it is important to measure phosphate concentration within the first days of life.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies confirmed that serum albumin correlated with short-term and long-term mortality of CAP. [14][15][16][17] In the CAP-China network, albumin level was also an independent predictor of 60-day mortality of CAP. 18 Serum albumin is closely related to the risk of death in T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…For hyperphosphatemia, most studies had proved that hyperphosphatemia was an independent risk factor for mortality or morbidity [1,7,11,14,15,[20][21][22][23][24][25][26]. For hypophosphatemia, some studies showed that it was an independent risk factor for mortality or morbidity [1,8,23,27], but some studies showed that it was not signi cantly associated with mortality or morbidity [15,20,22,28]. Thus, it was not determined whether serum phosphate abnormalities are directly related to the increase in mortality in ICU patients or merely a sign of the severity of disease for ICU patients.…”
Section: Introductionmentioning
confidence: 99%